Induction of systemic acquired resistance in Zea mays also enhances the plant’s attractiveness to parasitoids - Rostás, Michael; Turlings, Ted (My University, 2008)
Plants under attack by caterpillars emit volatile compounds that attract the herbivore’s natural enemies. In maize, the caterpillar-induced production of volatiles involves the phytohormone jasmonic acid (JA). In contrast, pathogen attack usually up-regulates the salicylic acid (SA)-pathway and results in systemic acquired resistance (SAR) against plant diseases. Activation of the SA-pathway has often been found to repress JA-dependent direct defenses, but little is known about the effects of SAR induction on indirect defenses such as volatile emission and parasitoid attraction. We examined if induction of SAR in maize, by chemical elicitation with the SA-mimic benzo-(1,2,3)-thiadiazole-7-carbothioic acid S-methyl ester (BTH), attenuates the emission of volatiles induced by Spodoptera littoralis or exogenously applied JA. In addition, we determined how these treatments affected the attractiveness of the plants to the parasitoid Microplitis rufiventris in a six-arm-olfactometer. BTH treatment alone resulted in significant systemic resistance of maize seedlings against the pathogen Setosphaeria turcica, but had no detectable effect on volatile emissions. Induction of SAR significantly reduced the emission rates of two compounds (indole and (E)-β-caryophyllene) in JA-treated plants, whereas no such negative cross-talk was found in caterpillar-damaged plants. Surprisingly, however, BTH treatment prior to caterpillar-feeding made the plants far more attractive to the parasitoid than plants that were only damaged by the herbivore. Control experiments showed that this response was due to plant-mediated effects rather than attractiveness of BTH itself. We conclude that in the studied system, plant protection by SAR activation is compatible with and can even enhance indirect defense against herbivores.
Keywords: BTH; Cross-talk; Jasmonic acid; Microplitis rufiventris; Salicylic acid; Spodoptera littoralis; Tritrophic interactions; Volatiles